Plasma n-3 and n-6 fatty acid profiles and their correlations to hair coat scores in horses kept under Malaysian conditions - Goh, Yong Meng; Goriman Khan, Mohd Azam; Sia, Juo Yiing; Kanaesalingam, Shri Kanth; Law, Fang Lin (Veterinary Association Malaysia, 2004)
A survey was carried out to determine the relationship between plasma fatty acid profiles and hair coat scores of horses kept under Malaysian conditions. Thirty-seven Thoroughbred horses with an average age of seven years were included in this study. The surveyed population comprised 27 geldings and 10 mares from the Kuala Lumpur City Hall stables at Titiwangsa (TTW, n=7) and Bandar Tun Razak (BTR, n=7), the Equine Unit, Universiti Putra Malaysia (UPM, n=7), the Royal Malaysian Police stables (RMP, n=8) and the Selangor Turf Club (STC, n=8). Plasma and feed fatty acid profiles were determined using gas chromatography and the hair coat score determined using a seven-point scoring system (1=worst hair coat condition; 7=best hair coat condition). Results showed that feed and plasma fatty acids profiles were variable across sampling locations. The n-6:n-3 ratios in feeds ranged from 6.8 (BTR) to 17.2 (UPM). Only plasma oleic and linolenic acids were different (P<0.05) across sampling locations. The STC horses had the best hair coat score (median score=7, P<0.05). It was found that total n-3 fatty acids were highly correlated with hair coat scores ( rho =0.686, P<0.01). A significant inverse correlation between n-6:n-3 ratio and hair coat scores ( rho =-0.755, P<0.01) was also noted. This meant that increasing plasma n-3 fatty acids and decreasing n-6:n-3 ratios were associated with better hair coat scores in these horses.